Contribution to the study of cysts paraovario - Herrera Calmet, Abelardo (2015)
Paraovario cysts are benign tumors that originate in the body Rosenmüller, epoophoron or paraovario (Wolff remains of the body) that is located between the leaves of the broad ligament and whose etiology is not known so far. In our series of Pavilion 5, Room II of the Archbishop Loayza Hospital, found that of 2,746 ginecópatas 19 were carriers of paraovarian cyst, ie 0.69%. We also note that for every 100 ovarian cysts about 7-8 paraovario cysts, which indicates qure they are still frequent. The age at which most often occurred between 20 to 30 years. Paraovario cysts are generally medium in size, confirms our cases and never reach the size of large ovarian cysts, although there are exceptional cases by volume (Forgue, Hummel and Lawson). Symptoms occur when the tumor has a certain volume and symptoms in our study were presented in order of frequency, as follows: pain, tumor, lower limb numbness, nausea and vomiting, urinary symptoms and vaginal bleeding. The diagnosis is very difficult. When they are palpable confused by their location, mobility and consistency with ovarian cysts to the point that it is almost impossible to differentiate. The gynecological exam can give high percentage of certainty when we found the separate cystic ovarian tumor. As auxiliary diagnostic methods note the pneumoginecografía with HSG and culdoscopy. The most common complication encountered by us is the torsion of the pedicle of the cyst. EI treatment paraovario cysts is surgical removal, trying to be conservative.